Association of plasma ortho-tyrosine/para-tyrosine ratio with responsiveness of erythropoiesis-stimulating agent in dialyzed patients - Kun, Szilárd (Redox Rep, 2014)
Objectives Patients with end-stage renal failure (ESRF) treated with erythropoiesis-stimulating agents (ESAs) are often ESA-hyporesponsive associated with free radical production. Hydroxyl free radical converts phenylalanine into ortho-tyrosine, while physiological isomer para-tyrosine is formed enzymatically, mainly in the kidney. Production of ‘para-tyrosine’ is decreased in ESRF and it can be replaced by ortho-tyrosine in proteins. Our aim was to study the role of tyrosines in ESA-responsiveness. Methods Four groups of volunteers were involved in our cross-sectional study: healthy volunteers (CONTR; n = 16), patients on hemodialysis without ESA-treatment (non-ESA-HD; n = 8), hemodialyzed patients with ESA-treatment (ESA-HD; n = 40), and patients on continuous peritoneal dialysis (CAPD; n = 21). Plasma ortho-, para-tyrosine, and phenylalanine levels were detected using a high performance liquid chromatography (HPLC)-method. ESA-demand was expressed by ESA-dose, ESA-dose/body weight, and erythropoietin resistance index(1) (ERI(1), weekly ESA-dose/body weight/hemoglobin). Results We found significantly lower para-tyrosine levels in all groups of dialyzed patients when compared with control subjects, while in contrast ortho-tyrosine levels and ortho-tyrosine/para-tyrosine ratio were comparatively significantly higher in dialyzed patients. Among groups of dialyzed patients the ortho-tyrosine level and ortho-tyrosine/para-tyrosine ratio were significantly higher in ESA-HD than in the non-ESA-HD and CAPD groups. There was a correlation between weekly ESA-dose/body weight, ERI(1), and ortho-tyrosine/para-tyrosine ratio (r = 0.441, P = 0.001; r = 0.434, P = 0.001, respectively). Our most important finding was that the ortho-tyrosine/para-tyrosine ratio proved to be an independent predictor of ERI(1) (β = 0.330, P = 0.016). In these multivariate regression models most of the known predictors of ESA-hyporesponsiveness were included. Discussion Our findings may suggest that elevation of the ratio of ortho-tyrosine/para-tyrosine could be responsible for decreased ESA-responsiveness in dialyzed patients.